If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + -7) = 39 Reorder the terms: x + (-7 + x) = 39 Remove parenthesis around (-7 + x) x + -7 + x = 39 Reorder the terms: -7 + x + x = 39 Combine like terms: x + x = 2x -7 + 2x = 39 Solving -7 + 2x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 2x = 39 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = 39 + 7 2x = 39 + 7 Combine like terms: 39 + 7 = 46 2x = 46 Divide each side by '2'. x = 23 Simplifying x = 23
| 2.3(x)=6.5(313) | | 9+8x=8x-16 | | -3m+8(5m-7)=-271 | | -7/10k+14=-21 | | -89=8(x-7)+3x | | 9x+9=6x+15 | | a(x-b)=x | | 3x+6=x+2(4+x) | | -4(1-6n)=-100 | | (2X+13)3-(X-4)4=2 | | -1m+9=0 | | (x+5)+(2x-3)=96 | | x-5=-4x-2 | | (2x+1)/7-(x-1)/2=(5x-1)/14-(x-2) | | y^2+7y+18=0 | | x^3-11x-18=0 | | (X-3)4-(X-7)6=1 | | 4x+(x-10)=180 | | -8(-1+8n)=264 | | 2(2x+10)=(4x+17) | | 4(9x-7)=2x(1+5x)-(1-x) | | 144-8x=8x+16 | | (2x+5)+(5x-79)=122 | | 5x-20=x+4(5+x) | | X-(13X-X)/3=(X+2)/6 | | 4x^2-10x= | | 1/2a-1/3a=-2 | | P=R/B | | 2(2x+10)=4x+17 | | 2x/7+1/7-x/2-1/2=5x/14-1/14-(x-2) | | 3x(2x-14)=-4(3x+7)-x | | 4x+3-2x=-x-(-3x+3) |